1990
DOI: 10.1093/infdis/162.6.1252
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus in the Brain: In Vitro Infection of Human Brain-Derived Cells

Abstract: Models for human cytomegalovirus (HCMV) brain infection have been developed in a variety of brain-derived cells in which the factors governing virus infectivity might be studied in vitro. Studies were initiated with brain endothelial cells, the likely portal of entry for virus into the central nervous system. Primary explant cultures of brain endothelial cells, derived from homogenates of healthy human brain, supported complete viral gene expression and cytopathic effect (CPE). Endothelial cells do not appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 25 publications
5
47
0
Order By: Relevance
“…[40][41][42][43][44][45] There is relatively little information in the literature pertaining to CMV and brain neoplasms. Astrocytoma and glioblastoma cell lines have been shown to be at least somewhat permissive to CMV infection in vitro, 46 and a recent seroepidemiologic study has demonstrated that patients with glioblastoma multiforme were somewhat more likely to have antibodies to CMV than controls. 47 More direct evidence suggesting an association of CMV with gliomas has been provided in a recent study by Cobbs et al 18 In this particular study, the CMVencoded IE1-72 protein was detected in the tumor cells of 27 of 27 gliomas of various grades by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44][45] There is relatively little information in the literature pertaining to CMV and brain neoplasms. Astrocytoma and glioblastoma cell lines have been shown to be at least somewhat permissive to CMV infection in vitro, 46 and a recent seroepidemiologic study has demonstrated that patients with glioblastoma multiforme were somewhat more likely to have antibodies to CMV than controls. 47 More direct evidence suggesting an association of CMV with gliomas has been provided in a recent study by Cobbs et al 18 In this particular study, the CMVencoded IE1-72 protein was detected in the tumor cells of 27 of 27 gliomas of various grades by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…U373MG cells expressing IE1 may provide an interesting model for study of the viral gene in glial tumors. The pathogenesis of glial tumors is likely to involve persistent infection allowing expression of only a limited number of viral genes, rather than productive infection, which may lead to cell death directly or indirectly by immune responses (Ogura et al, 1986;Poland et Wolff et al, 1994). U373MG-IE1 cells used in this study may simulate such an in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…Various HCMV-infected cells were detected in the histological sections of affected brains. Indeed, endothelial, astroglial and neuronal cells in the human brain have been infected by HCMV in vitro (Schmidbauer et al, 1989;Poland et al, 1990;Plachter et al, 1996). Recently, a high percentage of malignant glioma samples were shown to have been infected by HCMV, and HCMV gene products including IE1 were indeed expressed in these tumors, suggesting that HCMV might play active roles in the pathogenesis of glioma (Cobbs et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Treatment of human astrocytes with selected proinflammatory cytokines (IL-1b, tumor necrosis factor (TNF)-a and interferon (IFN)-c) induces an antiviral state by blocking viral replication at the level of transcription from the major immediate early promoter (MIEP). 37,38 Endothelial cells of the brain microvasculature also support lytic infection, [39][40][41] and CMV infection of endothelial cells may be a potential means the virus uses to enter the CNS. Interestingly, HCMV infection of endothelial cells also promotes monocyte recruitment, transendothelial migration and infection, which may be another mechanism of viral dissemination into the brain.…”
Section: Shows No Cell Tropism In the Cnsmentioning
confidence: 99%